2017
DOI: 10.3389/fphar.2017.00242
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint in Glioblastoma: Promising and Challenging

Abstract: Glioblastoma (GBM) is a severe malignant brain cancer with poor overall survival. Conventional intervention remains dismal to prevent recurrence and deterioration of GBM cell. Recent years have witnessed exciting breakthroughs in novel immune strategies, especially checkpoint inhibitors, some of which have become adjuvant setting after standard of care in melanoma. Several clinical trials of checkpoint inhibitors are ongoing in glioblastoma and other brain carcinomas. Plus, synergistic combinations of checkpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
147
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(148 citation statements)
references
References 110 publications
(176 reference statements)
0
147
0
1
Order By: Relevance
“…In recent years, the use of immune checkpoint inhibitors (ICIs) has been popular in the treatment of malignant tumors . Some ICIs, such as anti‐ PD‐1 antibody, are superior to traditional chemoradiotherapy in terms of its clinical curative effect . However, certain types of malignant tumors, such as glioblastoma, are resistant to monotherapy with ICIs .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the use of immune checkpoint inhibitors (ICIs) has been popular in the treatment of malignant tumors . Some ICIs, such as anti‐ PD‐1 antibody, are superior to traditional chemoradiotherapy in terms of its clinical curative effect . However, certain types of malignant tumors, such as glioblastoma, are resistant to monotherapy with ICIs .…”
Section: Discussionmentioning
confidence: 99%
“…Some ICIs, such as anti‐ PD‐1 antibody, are superior to traditional chemoradiotherapy in terms of its clinical curative effect . However, certain types of malignant tumors, such as glioblastoma, are resistant to monotherapy with ICIs . Therefore, new immunotherapeutic targets are urgently needed to treat glioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated and check point inhibitor reinvigorated T cells may then reach CNS via lymphatic vessels. 9 Johanns et al 8 reported an increased lymphocyte infiltration and radiographic response in a glioblastoma with mutator phenotype subsequent to pembrolizumab application. This is suggestive of active CNS immune response following checkpoint blockade therapy.…”
Section: A S E Rep Ortmentioning
confidence: 99%
“…And, several pan-HDAC inhibitors, such as sodium valproate, etinostat, panobinostat, and vorinostat, have all been shown in vivo to enhance the antitumor efficacy of checkpoint inhibitory antibodies, as well as promote activated T cell infiltration into the tumors (Booth, Roberts, Poklepovic, & Dent, 2017; Booth, Roberts, Poklepovic, Kirkwood, & Dent, 2017; Christiansen et al, 2011; Gameiro, Malamas, Tsang, Ferrone, & Hodge, 2016; Hornig, Heppt, Graf, Ruzicka, & Berking, 2016; Kroesen et al, 2016; Vo et al, 2009; West & Johnstone, 2014; West et al, 2013). Tumor types tested in these studies are diverse and include melanoma, breast, colorectal, glioblastoma, and hepatoma (Chae, Wang, Nimeiri, Kalyan, & Giles, 2017; Huang et al, 2017; Keller, Zhang, Li, Schaider, & Wells, 2017; Monnot & Romero, 2017; Rai et al, 2017). …”
Section: Text Elementsmentioning
confidence: 99%